The level of two trace elements in carious, non-carious, primary, and permanent teeth - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (ISTANBUL UNIV PRESS, ISTANBUL UNIV RECTORATE, 2020)
Purpose The boron and fluoride mainly accumulate in the bones and teeth of the human body. The purpose of this study is to determine boron or fluoride levels in the whole tooth, to evaluate the correlation between their levels and to compare these levels in primary/permanent, carious, and non-carious groups. Materials and Methods The boron and fluoride levels of thirty-six teeth, separated such as primary carious (n=9) and non-carious (n=9), permanent carious (n=9) and non-carious (n=9), were determined by ICP-MS and ion-selective electrode, respectively. Results While boron levels were between 0.001 and 5.88 ppm, the fluoride levels were between 21.24 and 449.22 ppm. The boron level of non- carious teeth was higher than those of carious teeth in primary and permanent tooth groups. However, this difference was not statistically significant (p>0.05). The fluoride level of non-carious teeth was higher than those of carious teeth in primary (p=0.062) and permanent teeth groups (p=0.046). Negative correlation, found between boron and fluoride in all groups, was significant only in non-carious teeth group (r=-0.488, p=0.040). Conclusion The results of our study proved the importance of fluoride as a protective factor for dental caries once more. The boron levels in non- carious teeth were also higher than carious teeth. However, it was not significant. Moreover, there was negative correlation between teeth boron and fluoride levels. Therefore, it is necessary to conduct more detailed studies on the tooth boron level and its relation with caries formation and with fluoride levels.
Keywords: Boron; Fluoride; Teeth; Trace elements; Dental health; BORON; DENTIN; ZINC; SEX